Berberine-Loaded Biomimetic Nanoparticles Attenuate Inflammation of Experimental Allergic Asthma via Enhancing IL-12 Expression - Hua Jin; Hua Jin; Jiale Li; Jiale Li; Miaoyuan Zhang; Miaoyuan Zhang; Renxing Luo; Renxing Luo; Peishan Lu; Peishan Lu; Wenting Zhang; Junai Zhang; et al. (Frontiers Media S.A., 2021)
Asthma is one of the most common chronic pulmonary disorders, affecting more than 330 million people worldwide. Unfortunately, there are still no specific treatments for asthma so far. Therefore, it is very important to develop effective therapeutics and medicines to deal with this intractable disease. Berberine (Ber) has fabulous anti-inflammatory and antibacterial effects, while its low water solubility and bioavailability greatly limit its curative efficiency. To improve the nasal mucosa absorption of poorly water-soluble drugs, such as Ber, we developed a platelet membrane- (PM-) coated nanoparticle (NP) system (PM@Ber-NPs) for targeted delivery of berberine to the inflammatory lungs. In vivo, PM@Ber-NPs exhibited enhanced targeting retention in the inflammatory lungs compared with free Ber. In a mouse model of house dust mite- (HDM-) induced asthma, PM@Ber-NPs markedly inhibited lung inflammation, as evident by reduced inflammatory cells and inflammatory cytokines in the lung compared with free Ber. Collectively, our study demonstrated the inhibitory actions of nasally delivered nanomedicines on HDM-induced asthma, primarily through regulating Th1/Th2 balance by enhancing IL-12 expression which could potentially reduce lung inflammation and allergic asthma.